Exploring the sources and benefits of cooperation: The role and challenges of relational and moral goods - Lopes, H.; Calapez, T. (International Journal of Social Economics, 2011)
Purpose – Attempts by mainstream economics to account for cooperative behavior expand the utility-maximizing framework without questioning the individualistic set-up on which it is grounded. This paper aims to develop a theory of cooperation that departs from the individualistic framework. “Communal principles” must be introduced in the analysis to account for cooperation and the relational, as opposed to atomistic, nature of individuals must be acknowledged. Design/methodology/approach – The empirical study, based on data from the European Working Conditions and European Social Surveys, aims at illustrating the social benefits of cooperation. A categorical components analysis was carried out to build indicators for the notions of relational and moral goods and civic participation. Regression models were subsequently estimated to study the association between relational/moral goods at work and civic participation. Findings – The empirical results show that high levels of relational and moral goods at work are associated with high levels of civic participation. However, substantial differences are observed between countries. Nordic countries exhibit high levels of both indicators while some Eastern and Southern European countries perform much more poorly. The study illustrates interaction between certain features of working life and civic behavior. Originality/value – The theoretical contribution of the paper lies in the proposal of a new account of the sources of cooperative behavior at work. It argues that cooperation within work organizations is supported by three common goods – a common goal, relational goods and moral goods. The “goodness” of these goods does not derive simply from their generating utility but from their being commonly shared.